Disponibilidade em um sistema de arquivos distribuído flexível e adaptável - Carvalho, Lúcio Rodrigo de [UNESP] (2014)
A distributed file system allows users and applications to store and share data, accessing such resources remotely as if they were local. The characteristics of a distributed file system can be varied. Thereby, it is impossible to design a system covering all desirable characteristics, such as transparency, performance, scalability, reliability and availability, for example. The Flexible and Adaptable distributed file system (FlexA) incorporate important characteristics of NFS, AFS, GFS and Tahoe-LAFS. It eliminates the need for main server (such as the master in GFS or the introducer in Tahoe-LAFS). File storage is provided by two group of server: a reading group, where only data is found, and a writing group, where data and metadata are stored. Availability is provided in FlexA through a mechanism similar to the one presented by Tahoe-LAFS. In the present study the improvements achieved through the availability and performance of FlexA are presented. Details about the changes in the FlexA as well as the obtained results indicate that the FlexA is an important option for distributed file system